Tacit collusion under fairness and reciprocity - Doruk çIriðs; Luís Santos-Pinto (Games, 2013)
This paper departs from the standard profit-maximizing model of firm behavior by assuming that firms are motivated in part by personal animosity-or respect-towards their competitors. A reciprocal firm responds to unkind behavior of rivals with unkind actions (negative reciprocity), while at the same time, it responds to kind behavior of rivals with kind actions (positive reciprocity). We find that collusion is easier to sustain when firms have a concern for reciprocity towards competing firms provided that they consider collusive prices to be kind and punishment prices to be unkind. Thus, reciprocity concerns among firms can have adverse welfare consequences for consumers.
Keywords: D43; D63; L13; L21; 330; fairness; reciprocity; collusion; repeated games